Research in personnel and human resources management. Vol. 26 - Martocchio, Joseph J. (Research in personnel and human resources management, 2007)
"Research in Personnel and Human Resources Management" is designed to promote theory and research on important substantive and methodological topics in the field of human resources management. A volume is published each year including papers on issues of cutting-edge importance by some of the very best scholars in the field. It is considered to be one of the most respectable publications in the field of human resources management and acts as a primary resource to both individuals and libraries.